2018
DOI: 10.1088/1361-6463/aae17d
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation behavior of Ni/Al2O3 catalyst in nonthermal plasma-enabled catalysis

Abstract: The oxidation behavior of Ni/Al 2 O 3 catalyst in CO 2 plasma was investigated compared with CO 2 thermal oxidation, aiming for providing new insight into oxidationreduction cycle of plasma catalysis of dry methane reforming (DMR). Temperature programmed reaction spectrometry was applied to enable a quantitative analysis of gas consumption which is related to the oxidation and reduction of Ni/Al 2 O 3 catalysts. The nonthermal plasma oxidation mechanism was further analyzed by Raman spectroscopy, showing the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 57 publications
0
33
0
Order By: Relevance
“…45,46 As a result, during plasma-assisted CO 2 + CH 4 conversion over Ni/Al 2 O 3 spheres, the active oxygen can diffuse into the relatively small pores (pore size < 1 μm < the Debye length), resulting in the formation of NiO even at 20 μm beneath the Al 2 O 3 surface. 99 In the case of micropores (<2 nm), which are characteristic of conventional zeolites, Knudsen diffusion significantly reduces the λ acc of plasma-induced species. 45,46 Inside these micropores, few plasma-derived radicals are sufficiently longlived to travel a large distance.…”
Section: Discharges and Excited Species Inside Catalystmentioning
confidence: 99%
See 1 more Smart Citation
“…45,46 As a result, during plasma-assisted CO 2 + CH 4 conversion over Ni/Al 2 O 3 spheres, the active oxygen can diffuse into the relatively small pores (pore size < 1 μm < the Debye length), resulting in the formation of NiO even at 20 μm beneath the Al 2 O 3 surface. 99 In the case of micropores (<2 nm), which are characteristic of conventional zeolites, Knudsen diffusion significantly reduces the λ acc of plasma-induced species. 45,46 Inside these micropores, few plasma-derived radicals are sufficiently longlived to travel a large distance.…”
Section: Discharges and Excited Species Inside Catalystmentioning
confidence: 99%
“…It is worth noting that pure metals can be oxidized rapidly in CO 2 plasma. , CH x adsorbed on supported metal nanoparticles may also spill over onto the metal oxide supports during reactions . Therefore, the involvement of metal oxides in CH 3 O formation should be considered.…”
Section: Mechanisms Along Different Time Scalesmentioning
confidence: 99%
“…In addition, beam studies have suggested that dissociative chemisorption of methane is promoted more efficiently by vibrational energy than translational energy [18][19][20]. As a result, reactions of vibrationally excited molecules have been postulated to be important in a wide range of plasma-catalytic processes, including CO 2 splitting, CH4 reforming, and N 2 activation [13,[21][22][23][24][25][26]. However, no detailed mechanistic evidence is available that conclusively supports these claims.…”
Section: Introductionmentioning
confidence: 99%
“…In particular the ability of certain plasmas to carry out thermodynamically highly unfavorable processes such as CO 2 dissociation with very high efficiency can be traced back to their strong nonequilibrium properties . In addition, when interfaced with a solid catalyst, a wealth of additional plasma-induced chemistry is obtained; here, too, stimulation of reactions by vibrational excitation has been postulated to be crucial for processes such as plasma-enabled catalytic ammonia synthesis, methane reforming, , and CO 2 reduction . However, the precise mechanisms of this type of vibrationally stimulated processes and their chemical ramifications are poorly understood.…”
mentioning
confidence: 99%
“…11 In addition, when interfaced with a solid catalyst, 12 a wealth of additional plasma-induced chemistry is obtained; here, too, stimulation of reactions by vibrational excitation has been postulated to be crucial for processes such as plasma-enabled catalytic ammonia synthesis, 13 methane reforming, 14,15 and CO 2 reduction. 16 However, the precise mechanisms of this type of vibrationally stimulated processes and their chemical ramifications are poorly understood. Detailed atomic-level simulation approaches are therefore desirable.…”
mentioning
confidence: 99%